2017
DOI: 10.1002/ca.22951
|View full text |Cite
|
Sign up to set email alerts
|

Clinical anatomy of fecal incontinence in women

Abstract: Fecal incontinence is a devastating condition that has a severe impact on quality of life. This condition disproportionately affects women and its incidence is increasing with the aging United States population. Fecal continence is maintained by coordination of a functioning anal sphincter complex, intact sensation of the anorectum, rectal compliance, and the ability to consciously control defecation. Particularly important are the puborectalis sling of the levator ani muscle complex and intact innervation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Defecation requires both voluntary and involuntary reflexes, both of which are affected by aging, which may lead to the development of constipation and/or fecal incontinence. 31 Both conditions are prevalent in the geriatric population, particularly in frail, disabled adults and those with dementia, with over 50% of institutionalized adults experiencing fecal incontinence or constipation. 32,33 Previous research has also found that polypharmacy is a risk factor for fecal incontinence and constipation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Defecation requires both voluntary and involuntary reflexes, both of which are affected by aging, which may lead to the development of constipation and/or fecal incontinence. 31 Both conditions are prevalent in the geriatric population, particularly in frail, disabled adults and those with dementia, with over 50% of institutionalized adults experiencing fecal incontinence or constipation. 32,33 Previous research has also found that polypharmacy is a risk factor for fecal incontinence and constipation.…”
Section: Discussionmentioning
confidence: 99%
“…Polypharmacy, however, was associated with emptying symptoms, including straining with bowel movements and pain with passing stool. Defecation requires both voluntary and involuntary reflexes, both of which are affected by aging, which may lead to the development of constipation and/or fecal incontinence 31 . Both conditions are prevalent in the geriatric population, particularly in frail, disabled adults and those with dementia, with over 50% of institutionalized adults experiencing fecal incontinence or constipation 32,33 .…”
Section: Discussionmentioning
confidence: 99%
“…Additional insights into the pathophysiology of fecal incontinence come from the evaluation of patients with spinal cord injuries and other neurologic diseases. Loss of rectal sensation may contribute to deficits in RAIR, while exaggerated, unopposed stimulation during distention may induce involuntary sphincter relaxation, and impaired spinal reflex activity may reduce rectal compliance [82,93,94]. Incontinence in this setting may therefore derive from any combination of the following, depending on the level and completeness of injury: decreased anal sphincter resting tone, loss of voluntary control, or loss of anorectal reflexes.…”
Section: Fecal Incontinencementioning
confidence: 99%
“…3,4 Anal continence control physiology is complex, and relies on the integrated action of several events, such as the action of the sphincter muscles and pelvic floor muscles, presence of the rectal-anal inhibitory reflex, rectal-anal angle, rectal capacity, sensory-motor function of the anorectal anatomical region, patient's neurologic status, stool consistency, and intestinal transit time. 5,6 Several factors contribute to the appearance of female fecal incontinence, with predominance of obstetric trauma; a sphincteric lesion may occur in 35% of women who had normal deliveries, which can progress to incontinence or not, along with diabetes mellitus, multiple sclerosis and dementia. 7 Inflammatory bowel diseases, postoperative hemorrhoidal disease, and resection of colon and rectum are also conditions associated with AI.…”
Section: Introductionmentioning
confidence: 99%